Pengaruh Penerapan Sapta Pesona Terhadap Kepuasan Wisatawan di Lokasi Wisata Taman Muko-Muko Kecamatan Tanjung Raya Kabupaten Agam - Helga Sri Wahyuni; Hijriyantomi Suyuthie; Kasmita Kasmita (Departemen Pariwisata Universitas Negeri Padang, 2023)
This research was conducted of dissatisfaction of tourists at Taman Muko-Muko who are influenced by the application of sapta pesona. This research aims to: 1) Know the Effect of Sapta Pesona Application on Tourist Satisfaction Visiting Muko-Muko Park, 2) Describe the Application of Sapta Pesona in Muko-Muko Park 3) Describe Tourist Satisfaction Visiting Muko-Muko Park. Research type is quantitative research with a causal associative approach. This research was carried out at the Muko-Muko Park tourist attraction, Tanjung Raya District, Agam Regency. The research population was tourists who had visited the Muko-Muko Park tourist attraction from January to June 2022 with a total of 6135 people. Selection of research samples using incidental sampling with a total sample of 84 people. Data collection uses a Likert Scale model questionnaire that has been tested for validity and reliability. The data analysis technique used simple linear regression analysis which was processed using the help of the SPSS version 22.00 program. The results showed that 1) there was a significant effect of the application of Sapta Pesona on tourist satisfaction of 29.8%, 2) the application of Sapta Pesona was in a good category with a level achievement score of 82.85% of the ideal score, 3) Tourist Satisfaction is in a good category with an achievement score of 83.68% of the ideal score.